AN ANALYSIS OF INTERPERSONAL MEANING IN PUBLIC SPEECHES OF OBAMA’S SPEECH (A Critical Discourse Analysis) - Rissa Amelya (Journal of English Education Program (JEEP), 2018)
This paper deals with an analysis of interpersonal meaning in public speeches of Obama’s speech to find out how is interpersonal meaning constructed in Obama’s speech. This study employed a Critical Discourse Analysis (CDA) method based on van Dijk framework (2000) and Systemic Functional Linguistic (SFL) based on Halliday’s framework (1994). The sample was one speech text of Obama’s speech on Osama bin Laden death. This study used textual analysis as the instrument.  This study indicates that: (1) concerning mood system, it is found that declarative mood was the most frequent. It has 96 clauses (97%), while imperative mood has 3 clauses (3.0%), and there was no interrogative mood found in the speech, in speech functions, statement has 96 clauses (97%), while command has 3 clauses (3.0%) and there was no question in the speech. (2) Regarding modality, the probability of modalisation are ‘can’ and ‘will’ is median value, the modal of inclination in modulation is ‘would’ is low value and obligation of modulation is ‘should’ is median value, (3) In relation to pronoun system, this study found that pronoun “I” was found 9 times (15.3%), “we” was found 26 times (44.1%), “our” was found 18 times (30.5%), “they” was found 4 times (6.78%), “us” and “he” was found once (1.7%) in the speech. An analysis of power and ideology also to measure power relation between speaker and audiences. The power is unequal (formal). Besides, from ideology side, the speaker was successfully presents some logical ideologies and ideas by explaining the reasons in attacking the United States.